Trends and Hotspots in Nanoparticles for the Targeted Delivery of Nucleic Acids: A Ten-Year Bibliometric Study - Huang, Yingzhao; Zhan, Qi; Wu, Chenzhou; Liao, Nailin; Jiang, Zhou; Ding, Haoran; Wang, Kunyu; Li, Yi (Frontiers in Pharmacology, 2022)
Nanoparticles for the gene therapeutics field have seen remarkable progress over the last ten years; however, low delivery efficiency and other reasons impede the clinical translation of nanocarriers. Therefore, a summary of hotspots and trends in this field is needed to promote further research development. In this research, from 2011 to 2021, 1,221 full records and cited references of Web-of-Science-indexed manuscripts regarding nanoparticle-targeted delivery systems were performed and analyzed by CiteSpace, VOSviewer and Map equation. In these software, keywords co-occurrence networks, alluvial diagram, co-citation networks, and structural variation analysis were carried out to emphasize the scientific community's focus on nanomedicine of targeted delivering nucleic acids. Keywords such as transfection efficiency, tumor cell, membrane antigen and siRNA delivery were highlighted in the density map from VOSviewer. In addition, an alluvial flow diagram was constructed to detect changes in concepts. In the co-citation network, cluster 1 (exosomes) and cluster 17 (genome editing) were new research fields, and the efforts in modifying nanoparticles were revealed in the structural variation analysis. Aptamer and SELEX (systematic evolution of ligands by exponential enrichment) represented a helpful system in targeted delivery. These results indicated that the transfection efficiency of nanocarriers required continuous improvements. With the approval of several nucleic acid drugs, a new content of nanoparticle carriers is to introduce gene-editing technology, especially CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/ CRISPR-associated protein 9). In addition, exosomes have great potential as targeted nanoparticles. By mapping knowledge domains of nanomedicine in targeted delivering nucleic acids, this study analyzed the intellectual structure of this domain in recent ten years, highlighted classical modifications on nanoparticles, and estimated future trends for researchers and decision-makers interested in this field.